Thermal Interface Materials
By using directionally arranged fill particles and more viscous latex layers in thermoelectric contact materials, the problems of unstable thermal conductivity and insufficient self-repairing ability of existing materials are solved, and efficient thermal conductivity and strong adaptability are achieved.
Patent Information
- Application Number
- JP2024556309
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-22
- Filing Date
- 2023-03-22
- Publication Date
- 2025-04-14
AI Technical Summary
Existing thermoelectric contact materials have problems such as unstable thermal conductivity, insufficient self-repair capability and insufficient flexibility to adapt to different temperature ranges when conducting heat efficiently.
Using a composite material containing the first latex and fill particles, the directional arrangement of the fill particles in the material can improve thermal conductivity and enhance adhesion by applying a more sticky latex layer on the surface of the material.
It achieves efficient thermal conductivity under different pressures and temperature conditions, while also having self-healing capabilities and flexibility to adapt to different temperature ranges.
Smart Images

Figure 2025510069000001_ABST
Abstract
Description
[Background technology]
[0001] The invention disclosed herein relates to thermal interface materials, and more particularly to composite materials for efficiently transferring heat away from a particular area, such as an electronic component or other surface exposed to heat. [Brief explanation of the drawings]
[0002] The following is a brief description of the drawings, in which like elements are numbered alike and which are presented for the purpose of illustrating exemplary embodiments disclosed herein and not for the purpose of limiting the invention.
[0003] [Figure 1] FIG. 1 is a schematic diagram showing an embodiment of a heat-generating component, a heat sink, and a thermal interface material. [Figure 2A] FIG. 2A is a diagram of an interface material according to various embodiments. [Figure 2B] FIG. 2B is an illustration of an interface material according to various embodiments. [Figure 3A] FIG. 3A illustrates aspects of an interface material according to various embodiments. [Figure 3B] FIG. 3B illustrates aspects of an interface material according to various embodiments. [Figure 3C] FIG. 3C illustrates aspects of an interface material according to various embodiments. [Figure 4] FIG. 4 is a schematic diagram of a thermal interface material pad according to various embodiments. [Figure 5] Figure 5 shows plots of thermal impedance vs. pressure for six samples of thermal interface material pads. The top three traces show the results for samples without any surface treatment. The bottom three traces show the results for samples with the types of surface treatments shown in Figure 4. [Figure 6]FIG. 6 is a schematic diagram of a thermal interface material pad according to various embodiments. [Figure 7A] FIG. 7A illustrates an initial step in a method for manufacturing a thermal interface pad according to various embodiments. [Figure 7B] FIG. 7B illustrates a final step in the method for manufacturing a thermal interface pad according to various embodiments. [Figure 8A] FIG. 8A illustrates an initial step in a method for manufacturing a thermal interface pad according to various embodiments. [Figure 8B] FIG. 8B illustrates a final step in the method for manufacturing a thermal interface pad according to various embodiments. [Figure 9] FIG. 9 illustrates a block of stacked thermal interface material layers, each layer composed of a dimensionally oriented dispersion of material, according to various embodiments. [Figure 10] FIG. 10 is a diagram of a thermal interface material pad containing dimensionally oriented material that can be cut from a block such as that shown in FIG. [Figure 11] FIG. 11 is a graph showing the thermal performance of the disclosed alignment pad compared to competitive products. [Figure 12] FIG. 12 is a graph showing the comparative performance of embodiments of thermal interface materials. [Figure 13] FIG. 13 is a graph illustrating the comparative performance of embodiments of thermal interface materials. [Figure 14] FIG. 14 is a graph illustrating the comparative performance of embodiments of thermal interface materials. [Figure 15] FIG. 15 is a chart illustrating the properties of thermal interface materials according to various embodiments. [Figure 16] FIG. 16 is a chart illustrating the properties of thermal interface materials according to various embodiments. DETAILED DESCRIPTION OF THE INVENTION
[0004] The components, methods, and devices disclosed herein can be more fully understood by reference to the accompanying drawings. These drawings (also referred to herein as "figures") are merely schematic representations based on convenience and ease of illustrating the disclosure and, as such, are not intended to illustrate the relative size and dimensions of the devices or their components and / or to define or limit the scope of the example embodiments. Although specific terminology is used in the following description for the sake of clarity, these terms are intended to refer only to the particular structure of the embodiments selected for illustration in the drawings and are not intended to define or limit the scope of the disclosure. In the drawings and the following description, it will be understood that like numerical designations refer to components of the same function.
[0005] The following examples are merely illustrative of the thermal interface materials disclosed herein and are not intended to limit the scope of the invention.
[0006] Before introducing thermal interface materials (TIMs), some terminology is explained to provide background to the teachings herein.
[0007] In general, the term "self-healing" refers to materials that have a built-in ability to automatically repair damage without external problem diagnosis or human intervention. Traditional materials typically degrade over time due to fatigue, environmental conditions, or damage incurred during operation. Microscopic cracks and other damage have been shown to alter the thermal, electrical, and acoustic properties of traditional materials, and crack propagation can ultimately lead to failure of traditional materials. Cracks are generally difficult to detect in their early stages, requiring manual intervention for periodic inspection and repair. In contrast, self-healing materials counteract degradation by initiating repair mechanisms in response to microscopic damage.
[0008] In general, "thermal conductivity" (often written as k, λ, or κ) refers to a material's ability to conduct heat. Thermal conductivity is primarily evaluated based on Fourier's law of heat conduction. In general, thermal conductivity is a tensor property, which indicates anisotropy of the property.
[0009] A material with low thermal conductivity transfers heat less well than a material with high thermal conductivity. Therefore, materials with high thermal conductivity are used in heat sink applications, while materials with low thermal conductivity are used as thermal insulators. The thermal conductivity of a material can depend on temperature. The reciprocal of thermal conductivity is called "thermal resistivity."
[0010] The thermal conductivity may be expressed as equation (1).
[0011]
number
[0012] Generally, the term "thermal impedance" as used herein refers to the sum of a material's thermal resistance and all contact resistances. If a material has a low thermal impedance, it is a better heat conductor for that application. Therefore, factors such as surface roughness, surface flatness, clamping pressure, the presence of adhesives, inhomogeneity, and material thickness are factors that affect a material's thermal impedance. In general, thermal impedance is a useful metric for evaluating thermal performance because it takes into account more variables specific to the application.
[0013] As used herein, an "isotropically oriented" set of elements is understood to be randomly or substantially randomly arranged such that the elements are not preferentially or substantially preferentially aligned along a particular direction in space.
[0014] As used herein, an "anisotropically oriented" set of elements is understood to be arranged such that the elements are substantially preferentially aligned along a particular direction in space.
[0015] Various embodiments disclose a thermal interface material (TIM). The TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, the first filler particles being substantially aligned in a first direction. A first adhesive layer is disposed on a first surface of the bulk material. The first adhesive layer has higher tack than the bulk material. The first adhesive layer includes a second acrylic rubber. The first direction is substantially perpendicular to a first surface of the first surface on which the first adhesive layer is disposed.
[0016] According to various embodiments, the plasticizer particles (e.g., plasticizer particles included in the bulk layer) have a specific gravity (25 / 25) of about 1.062 as measured in accordance with ASTM D4052. In some embodiments, the plasticizer particles have a specific gravity (25 / 25) of 1.050 to 1.070 as measured in accordance with ASTM D4052. According to various embodiments, the plasticizer particles have a viscosity (25°C) of about 930 as measured in accordance with ASTM D4455. In some embodiments, the plasticizer particles have a viscosity (25°C) of 900 to 1000 as measured in accordance with ASTM D4455.
[0017] According to various embodiments, the plasticizer particles (e.g., plasticizer particles included in the bulk layer) have a viscosity (25°C) measured according to ASTM D4455 of about 850. In some embodiments, the plasticizer particles have a viscosity (25°C) measured according to ASTM D4455 of 850 to 1000.
[0018] In some embodiments, the plasticizer particles (eg, plasticizer particles included in the bulk layer) have a viscosity (25° C.) of 800 to 1000 as measured according to ASTM D4455.
[0019] In some embodiments, the TIM has a tensile strength parallel to the thickness of the TIM that is different from the tensile strength parallel to the width or length of the TIM (e.g., perpendicular to the thickness of the TIM). In some embodiments, the TIM has a tensile strength parallel to the width of the TIM that is different from the tensile strength parallel to the length of the TIM. For example, a first tensile strength of the TIM along a first direction is different from a second tensile strength of the TIM along a direction perpendicular to the first direction. In some embodiments, the tensile strength of the TIM along the first direction is less than the tensile strength of the TIM along a direction perpendicular to the first direction. For example, the first tensile strength of the thermal interface material along a first direction is different from the second tensile strength of the thermal interface material along a direction perpendicular to the first direction. The ratio of the second tensile strength to the first tensile strength may be at least 1.5:1. The ratio of the second tensile strength to the first tensile strength may be at least 2:1. The ratio of the second tensile strength to the first tensile strength may be at least 2.5:1. The ratio of the second tensile strength to the first tensile strength may be at least 3:1.
[0020] In some embodiments, the TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, the first filler particles being substantially aligned in a first direction. In some embodiments, the first filler particles include a first subset of first filler particles and a second subset of first filler particles. The first subset of first filler particles and the second subset of first filler particles differ in at least one attribute. As an example, the average size of the first subset of first filler particles is larger than the average size of the second subset of first filler particles. As another example, the thermal conductivity of the first subset of first filler particles is more uniform than the thermal conductivity of the second subset of first filler particles.
[0021] In some embodiments, the TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, and the first filler particles are substantially aligned in a first direction. The first direction may correspond to a direction in which heat is desired to be conducted or a direction in which heat is maximized within the TIM. For example, the first direction may correspond to the thickness of the TIM. In some embodiments, the bulk layer may include a set of slices or layers stacked or compressed together. The direction in which the slices or layers are stacked / compressed may be substantially parallel to an orthogonal vector (sometimes referred to herein as the first direction) relative to the surface of the corresponding slice or layer. In some embodiments, the first direction substantially corresponds to an axis along which the various slices or layers are joined to one another. Each slice / layer within the set of slices or layers is substantially identical (e.g., manufactured according to the same method). For example, each set of slices or layers may include a first acrylic rubber, plasticizer particles, and first filler particles. By way of example, the alignment of the first filler particles in the first direction includes more than 50% of the first filler particles being aligned in the first direction.
[0022] In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 75% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction. In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 85% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction. In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 90% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction.
[0023] In some embodiments, the substantial arrangement of the first filler particles in the first direction comprises at least 75% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises the longest side of the first filler particles being within 5 degrees of the first direction, in some embodiments, the substantial arrangement of the first filler particles in the first direction comprises at least 85% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises the longest side of the first filler particles being within 5 degrees of the first direction, in some embodiments, the substantial arrangement of the first filler particles in the first direction comprises at least 90% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises the longest side of the first filler particles being within 5 degrees of the first direction. In some embodiments, substantial alignment of the first filler particles in the first direction includes at least 90% of the first filler particles being aligned in the first direction, and alignment of the first filler particles in the first direction includes the longest side of the first filler particles being within 5 degrees of the first direction.
[0024] The bulk layer of the TIM includes first filler particles. In some embodiments, the bulk layer is 80% by weight of the first filler particles. The first filler particles can be comprised of ceramic particles. The first filler particles can be planar.
[0025] According to various embodiments, a TIM is disclosed, the TIM including a bulk layer, a first adhesive layer applied to a first side of the bulk layer, and a second adhesive layer applied to the first side of the bulk layer, the second side of the bulk layer being opposite the first side of the bulk layer.
[0026] Various embodiments disclose a thermal interface material (TIM). The TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, the first filler particles being substantially aligned in a first direction. A first adhesive layer is disposed on a first surface of the bulk material. The first adhesive layer has higher tack than the bulk material. The first adhesive layer includes a second acrylic rubber. The first direction is substantially perpendicular to a first surface of the first surface on which the first adhesive layer is disposed.
[0027] In some embodiments, the TIM has a tensile strength parallel to the thickness of the TIM that is different from the tensile strength parallel to the width or length of the TIM (e.g., perpendicular to the thickness of the TIM). In some embodiments, the TIM has a tensile strength parallel to the width of the TIM that is different from the tensile strength parallel to the length of the TIM. For example, a first tensile strength of the TIM along a first direction is different from a second tensile strength of the TIM along a direction perpendicular to the first direction. In some embodiments, the tensile strength of the TIM along the first direction is less than the tensile strength of the TIM along a direction perpendicular to the first direction. For example, the first tensile strength of the thermal interface material along a first direction is different from the second tensile strength of the thermal interface material along a direction perpendicular to the first direction. The ratio of the second tensile strength to the first tensile strength can be at least 1.5:1. The ratio of the second tensile strength to the first tensile strength can be at least 2:1. The ratio of the second tensile strength to the first tensile strength may be at least 2.5: 1. The ratio of the second tensile strength to the first tensile strength may be at least 3:1.
[0028] In some embodiments, the TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, wherein the first filler particles are substantially aligned in a first direction. In some embodiments, the first filler particles include a first subset of first filler particles and a second subset of first filler particles. The first subset of first filler particles and the second subset of first filler particles differ in at least one attribute. For example, the average size of the first subset of first filler particles is larger than the average size of the second subset of first filler particles. As another example, the thermal conductivity of the first subset of first filler particles is more uniform than the thermal conductivity of the second subset of first filler particles.
[0029] In some embodiments, the TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, and the first filler particles are substantially aligned in a first direction. The first direction may correspond to a direction in which heat conduction is desired or a direction in which heat is maximized within the TIM. For example, the first direction may correspond to the thickness of the TIM. In some embodiments, the bulk layer may include a set of slices or layers stacked or compressed together. The direction in which the slices or layers are stacked / compressed may be substantially parallel to an orthogonal vector (sometimes referred to herein as the first direction) relative to the surface of the corresponding slice or layer. In some embodiments, the first direction substantially corresponds to an axis along which the various slices or layers are joined to one another. Each slice / layer within the set of slices or layers is substantially identical (e.g., manufactured according to the same method). For example, each slice or layer set may include a first acrylic rubber, plasticizer particles, and first filler particles. As an example, arranging the first filler particles in a first direction includes 50% or more of the first filler particles being aligned in the first direction.
[0030] In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 75% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction. In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 85% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction. In some embodiments, substantially arranging the first filler particles in the first direction comprises at least 90% of the first filler particles being aligned in the first direction, where the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being parallel to the first direction.
[0031] In some embodiments, substantially disposing the first filler particles in the first direction comprises at least 75% of the first filler particles being aligned in the first direction, wherein the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction. In some embodiments, substantially disposing the first filler particles in the first direction comprises at least 85% of the first filler particles being aligned in the first direction, wherein the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction. In some embodiments, substantially disposing the first filler particles in the first direction comprises at least 90% of the first filler particles being aligned in the first direction, wherein the alignment of the first filler particles in the first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction. In some embodiments, substantial alignment of the first filler particles in the first direction includes at least 90% of the first filler particles being aligned in the first direction, and alignment of the first filler particles in the first direction includes the longest side of the first filler particles being within 5 degrees of the first direction.
[0032] The bulk layer of the TIM includes first filler particles. In some embodiments, the bulk layer is 80% by weight of the first filler particles. The first filler particles include ceramic particles. The first filler particles may be planar.
[0033] According to various embodiments, a TIM is disclosed, the TIM including a bulk layer, a first adhesive layer applied to a first side of the bulk layer, and a second adhesive layer applied to a second side of the bulk layer, which may be opposite the first side of the bulk layer.
[0034] Various embodiments include a power supply including a TIM as disclosed herein. The TIM can enhance thermal conductivity between two components. For example, the TIM conducts heat generated from one or more other components (e.g., integrated circuits, etc.). Because power supplies generate a relatively large amount of heat, a TIM is used to conduct heat from the heat source (or a component proximate the heat source that itself becomes increasingly hot) to a heat dissipation device, such as a heat sink.
[0035] Various embodiments include a control system for controlling one or more motors. The control system includes a thermal insulator (TIM) as disclosed herein. The TIM can enhance thermal conductivity between two components. For example, the TIM conducts heat generated from one or more other components (e.g., integrated circuits, etc.). Because motor control systems generate a relatively large amount of heat, a TIM is used to conduct heat from the heat source (or a component proximate the heat source that itself becomes increasingly hot) to a heat dissipation device, such as a heat sink.
[0036] Various embodiments encompass a semiconductor circuit. The semiconductor circuit may include an integrated circuit used in connection with generating power or controlling a power system. The semiconductor circuit includes a thermal insulator (TIM), as disclosed herein. The TIM may enhance thermal conductivity between two components. For example, the TIM conducts heat generated from one or more other components (e.g., integrated circuits). Because power semiconductors generate relatively large amounts of heat, a TIM is used to conduct heat from a heat source (or a component proximate to the heat source that itself becomes increasingly hot) to a heat dissipation device, such as a heat sink.
[0037] Various embodiments include an optical display. The optical display may include an LED light source, a laser light source, an incandescent light bulb, etc. Various other light sources can be implemented. The control system includes a TIM as disclosed herein. The TIM may increase thermal conductivity between two components. For example, the TIM conducts heat generated from one or more other components (e.g., an integrated circuit, a light source, etc.). Because optical displays generate a relatively large amount of heat, a TIM is used to conduct heat from the heat source (or a component proximate to the heat source that itself becomes increasingly hot) to a heat dissipation device, such as a heat sink.
[0038] According to various embodiments, the TIM has a thermal conductivity of at least 10 W / mK. In some embodiments, the TIM has a length of 12 inches or more and a width of 12 inches or more. In some embodiments, the TIM has a length of up to 12 inches and / or a width of up to 12 inches.
[0039] According to various embodiments, the TIM has a thickness of 0.5 mm to 5 mm. The TIM can be an approximately 12 inch by 12 inch pad with a thickness of 0.5 mm to 5 mm.
[0040] According to various embodiments, the TIM operably conducts heat from at least −40° C. to at least 150° C. In some embodiments, the thermal conductivity of the TIM in a −40° C. environment is within 10% of the thermal conductivity of the TIM in a 20° C. environment. In some embodiments, the thermal conductivity of the TIM in a −40° C. environment is within 5% of the thermal conductivity of the TIM in a 20° C. environment. In some embodiments, the thermal conductivity of the TIM in a −40° C. environment is within 20% of the thermal conductivity of the TIM in a 20° C. environment. In some embodiments, the thermal conductivity of the TIM in a 150° C. environment is within 10% of the thermal conductivity of the TIM in a 20° C. environment. In some embodiments, the thermal conductivity of the TIM in a 150° C. environment is within 5% of the thermal conductivity of the TIM in a 20° C. environment. In some embodiments, the thermal conductivity of the TIM in a 150° C. environment is within 20% of the thermal conductivity of the TIM in a 20° C. environment.
[0041] In some embodiments, the TIM has a dielectric strength of at least 200 V / mil.
[0042] Various embodiments disclose a thermal interface material (TIM). The TIM includes a bulk layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, wherein the first filler particles are substantially aligned in a first direction. The TIM is used in power supplies, automotive electronics, motor control systems, power semiconductors, optical power sources, and the like. In some embodiments, the surface of the TIM where the TIM is applied to a heat source is perpendicular to the first direction. For example, the normal to the surface where the TIM is applied is parallel to the first direction. The tensile strength of the TIM in the first direction is greater than the tensile strength in a second direction, and the second direction is perpendicular to the first direction. In some embodiments, the tensile strength of the TIM in the first direction is at least 25% greater than the tensile strength of the TIM in the second direction. In some embodiments, the tensile strength of the TIM in the first direction is at least 50% greater than the tensile strength of the TIM in the second direction. In some embodiments, the tensile strength of the TIM in a first direction is at least 15% greater than the tensile strength of the TIM in a second direction, and in some embodiments, the TIM is flexible (e.g., the TIM is adapted to conform to a surface, such as a curved surface).
[0043] Various embodiments disclose a thermal interface material (TIM). The TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, where the first filler particles are substantially aligned in a first direction. A first adhesive layer of the at least one adhesive layer is disposed on a first side of the bulk material. The first adhesive layer has higher tack than the bulk material. The first adhesive layer includes a second acrylic rubber. The first direction is substantially perpendicular to a first surface of the first side on which the first adhesive layer is disposed. In some embodiments, the first adhesive layer is applied (e.g., to the bulk layer) by a pressure-sensitive adhesive (e.g., spray or roll coating). In some embodiments, the first adhesive layer is a polymer solution applied to the bulk layer.
[0044] A very thin layer of adhesive (e.g., a polymer solution) can be applied by spraying the adhesive onto the surface of the bulk layer. In some embodiments, the thermal conductivity of at least one adhesive layer is lower than the thermal conductivity of the bulk layer.
[0045] Various embodiments disclose a thermal interface material (TIM). The TIM includes a bulk layer and at least one adhesive layer. The bulk layer includes a first acrylic rubber, plasticizer particles, and first filler particles, the first filler particles being substantially aligned in a first direction. A first adhesive layer of the at least one adhesive layer is disposed on a first surface of the bulk material. The first adhesive layer has higher tack than the bulk material, and the first adhesive layer includes a second acrylic rubber. The first direction is substantially perpendicular to a first surface of the first surface on which the first adhesive layer is disposed. In some embodiments, the thermal conductivity of the at least one adhesive layer is lower than that of the bulk layer. For example, the thermal conductivity of the first adhesive is at least 10% lower than that of the bulk layer. For another example, the thermal conductivity of the first adhesive is at least 25% lower than that of the bulk layer. By way of example, the thermal conductivity of the first adhesive is at least 50% lower than the thermal conductivity of the bulk layer.
[0046] In some embodiments, when the heat source is a relatively hard material, the at least one adhesive is a polymer solution that is applied by spraying the polymer solution onto the surface of the bulk layer. The relatively hard material may have a Shore 00 value greater than 70.
[0047] In some embodiments, the TIM has a thermal conductivity of at least 15 W / M·K as measured by ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal conductivity of 17 W / M·K as measured by ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal resistance to pressure of at least 0.95 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 / W. In some embodiments, the TIM has a thermal resistance to pressure of 0.96 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 / W. In some embodiments, the TIM has a compression deflection of at least 10% at 210 kPa (30 psi) as measured by a modified ASTM C165 method. In some embodiments, the TIM has a compression deflection of 15% at 210 kPa (30 psi) as measured by a modified ASTM C165 method. In some embodiments, the TIM has an operating temperature of -40°C to 135°C. In some embodiments, the TIM has a Shore 00 hardness of 70 to 90 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of at least 75 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of less than 100 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of 77 to 87 as measured by ASTM D2240. In some embodiments, the TIM has a surface roughness of at least 1.5 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of at least 1.70 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of 1.71 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of 2.0 g / cm, measured according to a method substantially based on ASTM D792. 2 It has a specific gravity of less than 10 ...
[0048] In some embodiments, the TIM has a thermal conductivity of at least 20 W / M·K as measured to ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal conductivity of at least 25 W / M·K as measured to ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal conductivity of at least 30 W / M·K as measured to ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal conductivity of 35 W / M·K as measured to ASTM D5470 at 20 psi. In some embodiments, the TIM has a thermal resistance to pressure of at least 0.25 Kcm at 140 kPa (20 psi) as measured to ASTM D5470. 2 In some embodiments, the TIM has a thermal resistance to pressure of at least 0.40 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 In some embodiments, the TIM has a thermal resistance to pressure of 0.45 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 In some embodiments, the TIM has a thermal resistance to pressure of 0.90 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 In some embodiments, the TIM has a thermal resistance to pressure of less than 0.75 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 In some embodiments, the TIM has a thermal resistance to pressure of less than 0.50 Kcm at 140 kPa (20 psi) as measured by ASTM D5470. 2 / W. In some embodiments, the TIM has a compression deflection of at least 10% at 210 kPa (30 psi) as measured by a modified ASTM C165 method. In some embodiments, the TIM has a compression deflection of at least 15% at 210 kPa (30 psi) as measured by a modified ASTM C165 method. In some embodiments, the TIM has a compression deflection of at least 15% at 210 kPa (30 psi) as measured by a modified ASTM C165 method. In some embodiments, the TIM has an operating temperature of -40°C to 150°C. In some embodiments, the TIM has a Shore 00 hardness of 70 to 90 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of at least 75 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of at least 100 as measured by ASTM D2240. In some embodiments, the TIM has a Shore 00 hardness of 77 to 83 as measured by ASTM D2240. In some embodiments, the TIM has a hardness of at least 1.5 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of at least 1.70 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of 1.7-g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of 2.0 g / cm, measured according to a method substantially based on ASTM D792. 2 In some embodiments, the TIM has a specific gravity of less than 1.75 g / cm, measured according to a method substantially based on ASTM D792. 2 It has a specific gravity of less than 10 ...
[0049] According to various embodiments, the TIM does not include silicone, e.g., the TIM is a non-silicone, non-reactive, non-curing system without segregation of resin fillers.
[0050] Various embodiments encompass TIMs with high thermal stability for continuous operation up to at least about 135°C. The TIMs according to various embodiments have relatively low density, improving the weight reduction of the TIMs and devices incorporating the TIMs. The TIMs enable rework of thermal interface management systems. In some embodiments, the TIMs provide easy pick-and-place applications with a tacky surface for ease of manufacturing. In some embodiments, the TIMs are relatively compressible, potentially minimizing contact resistance without significant force and component stress.
[0051] FIG. 1 is a schematic diagram illustrating the use of a heat generating component, a heat sink, and a thermal interface material.
[0052] In the illustrated thermal management system 100, a heat source 150 generates heat. Non-limiting examples of the heat source 150 include at least one of a processor, a memory, a power supply, a power converter, a light emitting diode, and a laser diode. Typically, the heat source 150 is attached to a substrate 140. A non-limiting example of the substrate 140 is a printed circuit board (PCB). In this illustration, the heat source 150 is surface mounted to the substrate 140. A first deposit of thermal interface material (TIM) 110 is directly above and in thermal communication with the heat source 150. A heat spreader 170 is disposed above and in thermal communication with the first deposit. A second deposit of thermal interface material (TIM) 110 is above and in thermal communication with the heat spreader 170. A heat sink 120 is above and in thermal communication with the second deposit.
[0053] When the heat source 150 is energized, it generates heat. The heat is conducted away from the heat source 150 by the thermal interface material (TIM) 110 and the stack of the heat spreader 170 and the heat sink 120. The stack of the thermal interface material (TIM) 110 generally improves thermal conduction between the heat source 150 and the heat sink 120 by eliminating gaps and air gaps between the components.
[0054] In general, the heat sink 120 is a conventional cooling solution that maximizes surface area (using fins or pins) and airflow (using a fan) to dissipate heat from the heat source 5 into the surrounding air. The heat sink 120 may be constructed using a cooling fan as a simple, lightweight, and completely self-contained cooling solution. Depending on the available airflow, the heat sink 120 often performs better than a similarly sized heat spreader 170.
[0055] Typically, heat spreader 170 has a large, flat surface on top. In some embodiments, heat spreader 170 does not have a fan or fins. Heat spreader 170 is pressed directly against another large, flat surface (e.g., the frame of a vehicle or the interior wall of an enclosed container), and heat is transferred from heat spreader 170 to the larger metal (thermally conductive) surface. In a typical design, heat spreader 170 does not cool only heat source 150 (e.g., a CPU). Rather, heat spreader 170 is designed to transfer heat to another object so that it can safely dissipate from heat source 150. Generally, heat spreader 170 is ideal for electronic systems that are expected to operate under extreme shock and vibration, or that need to be completely sealed within a container for environmental protection. It will be appreciated that the performance of the heat sink 120 and heat spreader 170, and therefore the heat source 120 (eg, processor), can be substantially dependent on the performance of the thermal interface material (TIM) 110.
[0056] It is readily apparent that having the thermal interface material (TIM) 110 available as a pad in the thermal management system 100 of Figure 1 speeds assembly and provides consistent quality. That is, applying the thermal interface material (TIM) 110 in the form of, for example, a grease or paste, requires not only uniform application but also volume control. In contrast, designing the thermal interface material (TIM) 110 to be implemented as a pad with appropriate physical properties allows for superior quality control.
[0057] 2A is a diagram of a thermal interface material according to various embodiments. In the illustrated example, TIM 200 includes adhesive layer 210 and bulk layer 220. As shown in FIG. 2A, bulk layer 220 may include multiple layers 221, 222, and 224. Adhesive layer 210 may be included on at least one side of bulk layer 220.
[0058] 2A, first adhesive layer 210 is applied to a surface of bulk layer 210 that is substantially perpendicular to the interfaces between various layers of bulk layer 220. For example, first adhesive layer 210 may be applied to a surface that is perpendicular to (i) the interface between layer 221 and a layer adjacent to layer 221, (ii) the interface between layer 222 and a layer adjacent to layer 222, and / or (iii) the interface between layer 224 and a layer adjacent to layer 224, etc.
[0059] FIG. 2B is a diagram of a thermal interface material according to various embodiments. In the illustrated example, the TIM 200 includes multiple adhesive layers included on different sides of the bulk layer 220. For example, the TIM 200 includes a first adhesive layer 210 on a first surface of the bulk layer 220 and a second adhesive layer 260 on a second surface of the bulk layer 220. The first surface and the second surface may be on opposite sides of the bulk layer 220. In some embodiments, the first adhesive layer 210 and the second adhesive layer 220 are on respective sides of the bulk layer 220 perpendicular to an interface between layers included in the bulk layer 220. For example, the first adhesive layer 210 and the second adhesive layer 220 are applied to a surface perpendicular to (i) the interface between layer 221 and a layer adjacent to layer 221, (ii) the interface between layer 222 and a layer adjacent to layer 222, and / or (iii) the interface between layer 224 and a layer adjacent to layer 224, etc.
[0060] 2A and 2B, according to various embodiments, first adhesive layer 210 and / or second adhesive layer 260 are polymer solutions applied to bulk layer 220. For example, the polymer solutions are applied using a spraying or rolling process. As another example, the polymer solutions are applied using an electrospinning or electrospraying process.
[0061] FIG. 3A illustrates aspects of a thermal interface material according to various embodiments. In the illustrated example, TIM 300 includes adhesive layer 310 and bulk layer 320. As shown in FIG. 3A, bulk layer 320 may include multiple layers 321, 322, 323, 324, and 325. Adhesive layer 310 may be included on at least one side of bulk layer 320. Adhesive layer 310 may correspond to or be similar to adhesive layer 210 of TIM 200 in FIG. 2A.
[0062] According to various embodiments, bulk layer 210 is manufactured according to methods further described herein or in U.S. patent application Ser. No. 17 / 165,363, filed February 2, 2021, which is incorporated herein in its entirety for all purposes. In some embodiments, a masterbatch of bulk material included in bulk layer 320 is extruded to form a sheet or film of a predetermined thickness. One or more sheets of bulk material are cut to obtain predetermined sizes / shapes of bulk material (also referred to herein as bulk material segments). Multiple bulk material segments are then stacked and compressed to form a bulk material assembly. The bulk material assembly is then sliced in a direction perpendicular to the interface between pairs of multiple bulk material segments to obtain bulk layer 320 (e.g., a TIM pad). An adhesive layer may then be applied to one or more surfaces of bulk layer 320, such as using methods described above with respect to TIM 200.
[0063] As shown in FIG. 3A , bulk layer 320 includes a first acrylic rubber, plasticizer particles, and first filler particles, where the first filler particles are substantially aligned in a first direction. For example, bulk layer 320 includes first filler particles 331, 332, 334, 335, and 336. As shown in FIG. 3A , first filler particles 331, 332, 334, 335, and 336 are substantially aligned in the first direction. The bulk layer may include multiple layers, such as layer 321, layer 322, layer 323, layer 324, and / or layer 325. The first direction can correspond to a direction (substantially) parallel to an interface between layers of bulk layer 320 (e.g., the interface or surface where layer 321 is attached to layer 322, or the interface or surface where layer 322 is attached to layer 323, etc.). The filler particles may be aligned based at least in part on the extrusion method used to extrude the bulk material.
[0064] 3B illustrates aspects of a thermal interface material according to various embodiments. According to various embodiments, the thermal interface material includes one or more air channels extending along a first direction. The first direction can be parallel (or substantially parallel) to the interface between the bulk layers. In some embodiments, the one or more channels extend along the first direction.
[0065] In some embodiments, one or more channels are contained within, adjacent to, or proximate to an interface between layers of a bulk layer.
[0066] 3B, TIM 300 includes air channels 341 and 342. Air channel 341 is contained within, adjacent to, or proximate to the interface of layers 321 and 322 of bulk layer 320. As an example, air channel 341 may be formed when a bulk material segment corresponding to layer 321 and a bulk material segment corresponding to layer 322 are compressed or fastened together.
[0067] Related art TIMs are generally uniform bulk or composite materials throughout the material. The presence of one or more channels (e.g., air channels) may improve the weight of the TIM. For example, the density of the air or other gas contained within the one or more channels is lower than the density of the bulk material of the bulk layer 320.
[0068] 3C illustrates aspects of a thermal interface material according to various embodiments. According to various embodiments, the thermal interface material can be parallel (or substantially parallel) to the first direction interface. In some embodiments, one or more channels extend along the first direction.
[0069] In some embodiments, one or more channels are contained within, adjacent to, or proximate to an interface between layers of a bulk layer.
[0070] 3C, TIM 300 includes bubbles (e.g., air bubbles) contained at or adjacent or proximate to the interface between two layers of bulk layer 320. For example, bubbles 351, 352, 353, and 354 are contained at or adjacent to the interface between layer 321 and layer 322. For example, bubbles 351, 352, 353, and 354 may form when a bulk material segment corresponding to layer 321 and a bulk material segment corresponding to layer 322 are compressed or fastened together.
[0071] According to various embodiments, the introduction of channels (e.g., air channels) or bubbles can be enhanced by performing a surface treatment on the bulk material segments that correspond to the layers of the assembled bulk layer, for example, by scoring the surface of the bulk material segments or by providing multiple depressions in the surface.
[0072] 4 is a schematic diagram of a thermal interface material pad according to various embodiments. Referring to FIG. 4, an example of a thermal interface material (TIM) 401 is shown. The TIM 401 is formed as a pad or sheet 402 that extends between a first major surface 403 (shown as the bottom surface) and a second major surface 404 (shown as the top surface). While a flat sheet is shown, it will be apparent to one skilled in the art that other shapes may also be used, such as a curved sheet or a sheet cut to a custom shape and size suitable for a particular application.
[0073] The sheet 402 is formed from a base material 405 and a thermally conductive filler material 406 embedded in the base material 405 .
[0074] The base material 405 may be a material selected to have desired mechanical and thermal properties. A number of suitable examples of materials are provided below. In the illustrated exemplary embodiment, the base material is believed to be an acrylic rubber or acrylic resin material. In some embodiments, the base material 405 may be a blend of components combining a resin and a plasticizer material.
[0075] Advantageously, in some embodiments, the base material can be free or substantially free of silicone or other siloxane-based polymers, which are known to exhibit degradation, outgassing, and other undesirable properties at high temperatures.
[0076] As shown, filler material 406 may include anisotropically oriented thermally conductive elements 407. Thermally conductive elements 407 may be preferentially oriented along a major direction from first major surface 403 to second major surface 404 (perpendicular, as shown), which may facilitate thermal conduction through the sheet along the major direction.
[0077] In some embodiments, the inclusion of fillers improves the thermal conductivity of the sheet 402 along the major direction. For example, in some embodiments, the thermal conductivity of the sheet along the major direction is at least 10 W / mK, 15 W / mK, 30 W / mK, 40 W / mK, 50 W / mK, 60 W / mK, 70 W / mK, 80 W / mK, 90 W / mK, 100 W / mK, or more. In some embodiments, thermal conductivity may be measured using ASTM standard D5470, which is known in the art.
[0078] In some embodiments, TIM 401 exhibits excellent thermal impedance as a function of applied pressure. For example, in some embodiments, this property may be measured using techniques described in ASTM standard D5470 known in the art, resulting in a thermal impedance at 10 psi of less than 0.1°C-inch² / W, 0.09°C-inch² / W, 0.08°C-inch² / W, 0.07°C-inch² / W, 0.05°C-inch² / W, or even less (e.g., for sheets having thicknesses ranging from 0.5 mm to 5.0 mm). For example, in some embodiments, this property may be measured using techniques described in ASTM standard D5470 known in the art, resulting in a thermal impedance at 30 psi of less than 0.06°C-inch² / W, 0.05°C-inch² / W, 0.04°C-inch² / W, 0.03°C-inch² / W, 0.02°C-inch² / W, 0.01°C-inch² / W, or less (e.g., for sheets having thicknesses ranging from 0.5 mm to 5.0 mm).
[0079] In some embodiments, the sheet 402 may be freestanding, for example, formed from a flexible polymer resin-based material 405. In some embodiments, the sheet may have a thickness in the range of 0.1 mm to 10 mm, or any subrange thereof, for example, 0.5 mm to 5.0 mm. In some embodiments, the TIM 401 may exhibit a Shore hardness in the range of 40 to 90, or any subrange thereof, for example, 50 to 80 or 60 to 70, as determined by the technique specified in ASTM D2240 (Shore 00).
[0080] In some embodiments, the density of TIM 401 may be in the range of 0.5 g / mL to 5.0 g / mL, or any subrange thereof, such as 1.0 g / mL to 2.0 g / mL, hi some embodiments, the density of TIM 401 may be about 1.7 g / mL.
[0081] In some embodiments, the TIM 401 exhibits a desirable high deflection as a function of applied pressure. In some such embodiments, this property allows for excellent thermal contact between the TIM 401 and other heat sources and sinks in pressure-applied applications. In some embodiments, the deflection as a function of compression may be measured using techniques known in the art from ASTM D5470 and ASTM C165 standards. In some embodiments, the TIM 402 exhibits a deflection of at least 10%, 20%, 30%, 40%, 50%, 60% or more at a compression pressure of 30 psi.
[0082] In some embodiments, TIM 401 can operate at temperatures ranging from −40° C. to 150° C. without significant degradation. For example, in some embodiments, TIM 401 exhibits less than 0.2% total mass loss at temperatures of 150° C., 160° C., 170° C., 180° C. or greater, as determined by thermogravimetric analysis using techniques specified in ASTM E595 standard known in the art.
[0083] In some embodiments, the filler material may include ceramic flakes, such as boron nitride flakes, hi some embodiments, the filler material may include boron nitride nanoflakes or nanoscrolls.
[0084] In some embodiments, the filler material may include carbon, such as graphite flakes or graphene flakes. In some embodiments, the filler material may include carbon nanotubes, bundles of carbon nanotubes, and aggregates of aligned carbon nanotubes. Other suitable examples of filler materials are provided in the examples below.
[0085] In some embodiments, the anisotropically oriented thermally conductive elements include flake-shaped elements having major surfaces, at least 65%, 75%, 85%, 95%, 99%, or more of the flake-shaped elements aligned such that the major surfaces lie substantially in a plane extending along a major direction across the first and second surfaces of the sheet. For example, as shown in Figures 1, 3A, 3B, and 3C, the majority of the conductive elements are oriented such that the major surfaces of the flakes lie across the top and bottom surfaces.
[0086] In some embodiments, the anisotropically oriented thermally conductive elements include elongated elements (e.g., carbon nanotubes) having a major dimension and one or more minor dimensions, where at least 65%, 75%, 85%, 95%, 99% or more of the elongated elements are aligned such that the major dimension extends along a major direction across the first and second surfaces of the sheet.
[0087] In various embodiments, the amount of filler material used may be selected to obtain desired properties. Generally, higher amounts of filler tend to result in higher thermal conductivity (provided that care is taken to ensure that the filler does not introduce undesirable surface roughness, as discussed in more detail below). In some embodiments, the filler is at least 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, or more by weight of the sheet.
[0088] Figure 5 shows plots of thermal impedance vs. pressure for six samples of thermal interface material pads. The top three traces show the results for samples without a surface treatment. The bottom three traces show the results for samples with an adhesive surface treatment.
[0089] Six TIM samples (e.g., TIM200 in Figure 2A, TIM300 in Figure 3A, etc.) were fabricated, each 1.0 mm thick. The samples were tested for thermal impedance at various pressures using techniques specified in ASTM standard D5470, which is known in the art. Three of the samples were surface treated to improve the surface finish, while the remaining three were untreated. As shown in Figure 5, the thermal impedance of the treated sample (bottom trace) is lower than that of the untreated sample (top trace), especially at low pressures. This clearly demonstrates that the surface treatment improves the thermal contact between the TIM101 used in the evaluation and the heat source and sink.
[0090] 6 is a schematic diagram of a thermal interface material pad according to various embodiments. Referring to FIG. 6, in some embodiments, the TIM 601 includes thermally conductive elements 620 that extend through the sheet 602 along a primary direction (shown as vertical) from the first major surface 603 to the second major surface 604. These thermally conductive elements may facilitate the flow of heat between the surfaces 603, 604. In some embodiments, these elements 620 may be made of carbon. For example, graphite or graphene formed into sheets, strips, pillars, or other suitable shapes may be used.
[0091] In some embodiments, portions of the thermally conductive element may be exposed at the first and second major surfaces 603, 604 of the sheet 602. In such cases, it may be desirable to treat the surfaces to protect these areas, such as by using a solvent-based surface treatment as described above or by applying a thin protective adhesive layer to surfaces 603, 604.
[0092] 7A and 7B illustrate an initial step and a final step of a method for manufacturing a thermal interface pad, respectively, according to various embodiments.
[0093] Referring to Figure 7A, a stack is formed to include multiple layers, which may correspond to layers in the bulk layer of the TIM.
[0094] Each layer extends from the bottom to the top in a certain direction (vertical as shown in the figure), and the layers are stacked in that direction.
[0095] Each layer includes a base material and a filler material of the type described above with reference to Figures 2A, 2B, 3A, 3B, and 3C. The filler material in each layer is composed of anisotropically oriented thermally conductive elements. However, unlike the sheets used in the final TIM, the elements are oriented to promote heat flow across the vertical direction from the bottom surface to the top surface, rather than along the vertical direction. Therefore, these layers in the stack are not suitable for use as the TIMs of Figures 2A, 2B, 3A, 3B, and 3C without further processing.
[0096] Thus, referring to FIG. 6B , in some embodiments, a force (and optionally heat) is applied in a vertical direction to compress the stack and bond the layers together to form a monolithic element. The monolithic element may include a plurality of channels (e.g., air channels or bubbles, such as bubbles or pockets). The stack may be sliced, for example, using a thin blade or ultrasonically or laser cutting along a vertically extending plane (indicated by the thick black arrow in FIG. 7B ) to form a sheet of desired thickness. This sheet is removed from the stack to form a TIM, such as the TIMs shown in FIGS. 2A, 2B, 3A, 3B, and 3C. Notably, the TIM may include a sheet having a filler material composed of anisotropically oriented thermally conductive elements oriented in a suitable direction. For example, the sheet may extend between first and second major surfaces, and the filler material may include anisotropically oriented thermally conductive elements that are preferentially oriented along a major direction from the first to the second major surface to promote heat conduction through the sheet along the major direction.
[0097] Additional slices may be taken to produce additional TIM pads. In other words, the stacking and slicing method described above takes multiple layers in which the filler material is anisotropically oriented in a direction unsuitable for use as a TIM, to produce multiple TIM pads in which the filler has the desired orientation.
[0098] As described in detail below, the layers can be produced using simple methods suitable for mass production techniques. For example, in some embodiments, each stack layer can be formed by providing a mixture of a base material and a filler material that encompasses the thermally conductive elements. Generally, this mixture can be made without a step to orient the filler material, resulting in an anisotropic distribution of the thermally conductive elements within the base material. The resulting mixture can then be physically manipulated to anisotropically orient the thermally conductive elements within the layer. For example, as described in detail in additional examples below, the mixture can be extruded to form layers, compressed to form layers, repeatedly folded to form layers, or combinations thereof.
[0099] As previously mentioned, this physical manipulation produces a layer with anisotropically oriented thermally conductive elements oriented in a direction that is undesirable for use in a TIM, however, this can be corrected by performing the stacking, compressing, and slicing steps previously described with reference to Figures 7A and 7B.
[0100] In some embodiments, the base material is a self-healing material, which facilitates fusing the layers into a monolithic element during the compression slicing process described above. Self-healing materials also have the advantage of resisting damage (e.g., cracking) that may occur during the slicing process described with reference to FIG. 7B.
[0101] In various embodiments, the method may further include applying a surface treatment to one or more major surfaces of the TIM, such as one or more adhesion layers, as further described herein.
[0102] FIG. 8A illustrates an initial step in a method for manufacturing a thermal interface pad according to various embodiments.
[0103] According to various embodiments, the thermally conductive composition may include fillers such as metal powders and mixtures thereof (e.g., aluminum powder; silver powder; copper powder); graphite flakes, ceramic powders (e.g., alumina; boron nitride, etc.). The composition may also include a self-supporting base material, including materials such as rubber (e.g., acrylic rubber), oil, polymer, thermoplastic resin, and thermosetting resin. Generally, the thermally conductive composition may be fabricated from a material that exhibits suitable properties. The properties may include, for example, flexibility and good thermal conductivity. A variety of other materials may also be used.
[0104] In some embodiments, a thermoplastic resin that is substantially solid at room temperature is used. Examples of suitable thermoplastic resins include acrylic resins, epoxy resins, silicone resins, fluororesins, etc. These may be used alone or in combination with other materials (where feasible).
[0105] Thermoplastic resins may be used in combination with the solid. Examples of usable thermoplastic polymers / resins include acrylic resins such as poly(2-ethylhexyl acrylate), 2-ethylhexyl acrylate-acrylic acid copolymer, polymethacrylic acid or its ester, and polyacrylic acid or its ester; silicone resins; fluororesins; polyethylene; polypropylene; ethylene-propylene copolymer; polymethylpentene; polyvinyl chloride; polyvinyl acetate; ethylene-vinyl acetate copolymer; polyvinyl alcohol; polyacetal; polyethylene terephthalate; polyethylene; polystyrene; and polyacrylonitrile. Examples of suitable materials include styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene (ABS resin) copolymers, styrene-butadiene block copolymers or hydrogenated versions thereof, styrene-isoprene block copolymers or hydrogenated versions thereof, polyphenylene ethers, modified polyphenylene ethers, aliphatic polyamides, and aromatic polyamides, polyamides, polycarbonates, polyphenylene sulfides, polysulfones, polyethersulfones, polyethernitriles, polyetherketones, polyketones, polyurethanes, liquid crystal polymers, and ionomers. These may be used alone or, where feasible, in combination with other materials.
[0106] In some embodiments, fluorothermoplastics are used, which may also provide certain other advantages, such as improved heat, oil, and chemical resistance.
[0107] Potentially useful thermoplastic fluororesins include, for example, fluorine-containing polymerizable monomers such as vinylidene fluoride, tetrafluoroethylene-propylene, tetrafluoroethylene-based elastomers, etc. More specifically, examples include polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, ethylene copolymer, tetrafluoroethylene copolymer, polyvinyl fluoride, tetrafluoroethylene-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, acrylic-modified polytetrafluoroethylene, polytetrafluoroethylene-modified ester, epoxy-modified silane-modified polytetrafluoroethylene, polytetrafluoroethylene, etc.
[0108] Additional materials that may be used as thermosetting resins include, for example, natural rubber, acrylate rubber, butadiene rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene propylene rubber, chlorinated polyethylene, chlorosulfonated polyethylene, butyl rubber, halogenated butyl rubber, polyisobutylene rubber, polyacrylic rubber, epoxy resin, polyimide resin, bismaleimide resin, benzocyclobutene resin, phenolic resin, unsaturated polyester, diallyl phthalate resin, polyimide resin, polyurethane, thermosetting polyphenylene ether, thermosetting polyphenylene ether, and the like.
[0109] In some embodiments, the thermally conductive composition includes polyvinyl acetate (PVA) or polyethenyl ethanoate (PVAc). Generally, PVA has the formula (C4H6O2) nPVA is an aliphatic rubbery synthetic polymer of the formula -[RCOOCHCH2]-, which belongs to the polyvinyl ester family and is a type of thermoplastic resin. In some embodiments, the thermally conductive composition is a non-silicone-based material. Another example is a soybean oil-based material.
[0110] The above materials may be used alone or in combination with these or other materials (where practicable).
[0111] Disposed within the thermally conductive composition is a dispersion of thermal fillers, which may be provided as nano- and / or micro-materials.
[0112] Generally, thermal fillers exhibit some shape or morphology, and thus have at least one dimensional aspect (e.g., thin flakes having a major surface and a minor dimension, or elongated elements having one major dimension and two lateral minor dimensions). Thermal fillers may be selected for dispersion and exhibit good to excellent thermal conductivity. Examples of nanomaterials include, but are not limited to, forms of carbon nanotubes (including single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT)), as well as nanohorns, nano-onions, carbon black, fullerenes, graphene, graphene oxide, and various processed forms of the foregoing. In some embodiments, nanomaterials further include metal nanoparticles, metal oxide nanoparticles, and / or at least one form of thermally conductive polymer. The thermal filler may be provided as a micromaterial, including, but not limited to, graphite, boron nitride, boron nitride flakes, boron nitride nanoscrolls, aluminum nitride, aluminum nitride whiskers, carbon nanotubes, metal particles, metal oxide particles, and / or at least one form of thermally conductive polymer.
[0113] As used herein, the term "micromaterial" refers to a dimensional thermal filler material exhibiting one or more dimensions in the range of about 0.1 microns to about 200 microns (e.g., microscale particles or flakes). Generally, the term "nanomaterial" refers to a dimensional thermal filler material exhibiting one or more dimensions in the range of about a few nanometers to about 100 nanometers (0.1 microns) (e.g., nanotubes, nanorods, nanoparticles, nanoshells, nanohorns, and nanoscopic flakes such as graphene flakes).
[0114] Given the small nature of thermal fillers, in some embodiments, it is not possible to control orientation when mixing the thermal fillers into the thermally conductive composition, and thus the dispersion of the thermal fillers results in randomly oriented dimensional material within the volume of the thermally conductive composition.
[0115] The random orientation of the thermal fillers within the thermally conductive composition precludes the benefits of directional thermal conductivity. More specifically, without directional orientation, the thermal fillers' dominance of isotropic thermal conductivity would result in heat being conducted in random directions. However, rearranging anisotropically oriented dimensional thermal fillers to form an oriented material may allow the potential of the thermal fillers to be utilized.
[0116] Exemplary techniques for providing oriented dimensional materials include hydraulic pressing or extrusion. In some embodiments, a hydraulic press begins with a volume of thermally conductive composition having randomly oriented dimensional material dispersed therein. The volume of material is pressed or extruded into a substantially planar shape. In some embodiments, the substantially planar shape is then folded back onto itself, effectively reforming the volume into, for example, a ball or cube. The volume of material is then pressed back into a substantially planar shape. Generally, repeated pressing and folding promotes the randomly oriented filler material into a planar orientation, as shown in the layers above, for example, with reference to Figures 8A and 8B.
[0117] To facilitate migration of the filler material in a desired direction, the mixture of the thermally conductive composition and the dispersion of randomly oriented dimensional material may be heated, for example, during a pressing or extrusion process as described above. Generally, heating the mixture of the thermally conductive composition and the dispersion of randomly oriented dimensional material reduces the viscosity of the thermally conductive composition, thereby facilitating migration of the randomly oriented dimensional material in a desired direction.
[0118] When the dimensional materials are provided in a directional arrangement, as indicated by the labels in Figure 8A, heat is generally conducted in the x-y plane due to the anisotropic thermal conductivity preference of the nanomaterials. This property is utilized to provide the thermal pads disclosed herein.
[0119] The oriented material is segmented and arranged in stacks 940. After being arranged in stacks 940, the oriented thermal interface material (TIM) 900 may be further segmented. For example, the stack 940 is cut along an imaginary plane, shown as plane A, which lies in the XZ plane. The result is shown in FIG. 8B.
[0120] FIG. 8B is a diagram of the final step of a method for manufacturing a thermal interface pad according to various embodiments. As shown in FIG. 8B, an alignment pad 1050 encompasses a portion of the stack 940. Generally, the alignment pad 1050 is fabricated to dimensions suitable for use in the thermal management system 100 shown in FIG. 1. The resulting vectors transfer heat from the heat source 150 substantially through the XY plane. While some of the thermal filler transfers heat substantially in the X direction, a roughly equal portion of the nanomaterial is expected to transfer heat substantially in the Y direction. In other words, the anisotropic thermal conductivity of the thermal filler allows the majority of the heat to be transferred through the XY plane, but limits heat transfer in the Z direction (for the same reasons). Therefore, heat recirculation within the alignment pad 1050 is limited.
[0121] The thermal conductivity performance of the alignment pad 1050 was evaluated in a series of tests using a standardized test bench. The tests included comparisons with competitive products. Each product placed on the test bench was subjected to some degree of compression. The compression exhibited is shown in Table 1 below. In the data tables below, "NaL Pad" refers to the alignment pad 1050. The test data for the thermal conductivity evaluation is shown in FIG. 11.
[0122] [Table 1]
[0123] 11 is a graph showing the thermal performance of the orienting pad disclosed herein compared to competitive products. As shown in FIG. 11, the resulting orienting pad 50 outperforms all of the competitive pad products tested. The data shows that the thermal conduction performance of the orienting pad 50 is substantially equivalent to the thermal performance of a potting material (i.e., covering the heat source 5 with the potting material).
[0124] FIG. 12 is a graph illustrating the comparative performance of embodiments of thermal interface materials. Referring to FIG. 12, a comparison is shown illustrating the effects achieved from dimensional thermal material orientation. The heat spreader 170 was omitted from the thermal management system 100 used to generate the data shown. Three samples of thermal interface material 110 were tested. The first sample included a standard (STD) with thermal filler material oriented substantially perpendicularly. The temperature difference between the heat source 150 and the heat sink 120 quickly reached equilibrium and was maintained at approximately 5°C. The second sample (45°) of thermal interface material 110 was fabricated using the slicing technique described herein, with the slices being taken at an angle of approximately 45°. The third sample of thermal interface material 110 included thermal filler material oriented substantially perpendicular (90°) to the desired direction of heat flux.
[0125] A small temperature difference between the heat source 5 and the heat sink 2 means a low thermal resistance. Therefore, since the first sample has the smallest temperature difference, it is clear that orienting the particles so that heat is transferred through the XY plane (as defined in FIG. 10) improves the thermal conductivity of the thermal interface material 110.
[0126] After introducing aspects of the thermal interface material, some further aspects and examples are provided.
[0127] Thermal interface materials may be formed as soft materials. Typically, thermal interface materials are self-healing during manufacturing (slicing and stacking procedures).
[0128] In general, thermal interface materials are useful in applications where gaps need to be filled. Thermal interface materials offer excellent conformability to irregular surfaces.
[0129] In some embodiments, the thermal interface material includes a flexible polymer sheet material with a thickness selectable from about 0.25 mm to about 5 mm and a thermal conductivity of up to about 60 W / mK or greater. Current high-performance TIM sheets are approximately 5 W / mK. The resulting four-fold performance improvement is an enabling technology for high-power applications. Virtually any power system can utilize a high-performance TIM.
[0130] Applications for thermal interface materials include, but are not limited to, power supplies, automotive electronics, motor controls, power semiconductors, heat sink interfaces, processing systems, and other electronic devices such as computers, amplifiers, video processing equipment, control systems, etc.
[0131] In some embodiments, the resulting product exhibits a thermal conductivity of at least 60 W / mK. The product is provided in sheets, in some embodiments, approximately the size of standard printer paper. The product has a thickness between about 0.25 mm and 5 mm, and can be thinner or thicker. The product may be useful in a temperature range of -60°C to 250°C (or any subrange thereof, e.g., -40°C to 150°C), and may be useful at lower or higher temperatures. Generally, the product does not outgas and does not exhibit creep upon thermal cycling. Generally, the product is flexible and conforms to surrounding components. Generally, the product is reworkable and may be used in existing conventional manufacturing methods.
[0132] FIG. 13 is a graph illustrating the comparative performance of embodiments of thermal interface materials.
[0133] As shown in FIG. 13, in the pore size range of 1 μm to 100 μm, the top two plots are for TIMs according to various embodiments, and the bottom two plots are for competitive off-the-shelf TIMs. Referring to FIG. 13, the competitive off-the-shelf TIMs exhibit a rapid decrease in cumulative mass-normalized pore volume as pore sizes increase from approximately 0.05 μm to 1 μm. In contrast, TIMs according to various embodiments maintain a relatively high cumulative mass-normalized pore volume from approximately 0.05 μm to 1 μm, and indeed until the pore size approaches approximately 11 μm. According to various embodiments, TIMs exhibit a high cumulative mass-normalized pore volume of 1000 mm at 1 μm pore size. 3 / g. According to various embodiments, the TIM has a cumulative mass-normalized pore volume of greater than or equal to 1500 mm 3 According to various embodiments, the TIM has a mass-normalized pore volume of greater than or equal to 2000 mm / g with a pore size of 0.1 μm. 3 / g. According to various embodiments, the TIM has a cumulative mass-normalized pore volume of 2250 mm 3 In some embodiments, the TIM has a cumulative mass-normalized pore volume of greater than 250 mm 3In some embodiments, the TIM has a cumulative mass-normalized pore volume of greater than or equal to 500 mm 3 / g and has a cumulative mass-normalized pore volume greater than (or equal to)
[0134] FIG. 14 is a graph illustrating the comparative performance of embodiments of thermal interface materials.
[0135] As shown in Figure 14, in the pore size range of 10 μm to 100 μm, the top two plots are for TIMs according to various embodiments, and the bottom two plots are for competitive off-the-shelf TIMs. Referring to Figure 14, the competitive off-the-shelf TIMs have significantly lower differential mass-normalized pore volume values compared to the TIMs according to various embodiments. For example, as shown in Figure 14, the TIMs according to the related art have a differential mass-normalized pore volume of approximately 250 mm when the pore size is 10 μm. 3 In contrast, the TIM according to various embodiments has a pore size of approximately 10 μm to 15 μm, resulting in a relatively high differential mass-normalized pore volume. In some embodiments, the TIM has a pore size of 10 μm and a mass-normalized pore volume of 250 mm 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than 500 mm 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than 100 mm 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than 1500 mm 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than or equal to 1500 mm / g with a pore size of 2250 μm. 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than (or equal to) 2250 mm 3 In some embodiments, the TIM has a differential mass-normalized pore volume of greater than 250 mm 3In some embodiments, the TIM has a differential mass-normalized pore volume of less than (or equal to) 100 mm / g with a pore size of 0.01 μm. 3 / g.
[0136] Figure 15 is a chart showing the properties of thermal interface materials according to various embodiments. Figure 16 is a chart showing the properties of thermal interface materials according to various embodiments.
[0137] Various other components may be included or required to provide aspects of the teachings herein. For example, additional materials, combinations of materials, and / or omissions of materials may be used to provide additional embodiments within the scope of the teachings herein.
[0138] Various modifications of the teachings herein may be contemplated. Generally, modifications are designed in response to the needs of a user, designer, manufacturer, or other similar interested party. The modifications may be intended to meet particular performance criteria that the interested party considers important.
[0139] No appended claim or claim element should be construed as invoking 35 U.S.C. Section 112(f) unless the words "means" or "step" are expressly used in a particular claim.
[0140] When introducing elements of the invention or embodiments thereof, the articles "a," "an," and "the" mean there is one or more of the element. Similarly, the adjective "another," when used to introduce an element, means there is one or more elements. The terms "comprising" and "having" are intended to be inclusive, meaning that additional elements may be present other than the listed elements. As used herein, the term "exemplary" does not mean the best example. Rather, "exemplary" refers to an embodiment that is one of many possible embodiments.
[0141] While the present invention has been described with reference to exemplary embodiments, those skilled in the art will recognize that various modifications can be made and equivalent substitutions can be made of elements of the present invention without departing from the scope of the invention. In addition, many modifications will be apparent to those skilled in the art to adapt a particular equipment, situation, or material to the teachings of the present invention without departing from the essential scope of the invention. Therefore, it is not intended that the invention be limited to the particular embodiment disclosed as the best mode contemplated for carrying out this invention, but rather, the invention is intended to include all embodiments falling within the scope of the appended claims.
Claims
1. Bulk layer and: the bulk layer comprises a first acrylic rubber, plasticizer particles, and first filler particles; the first filler particles are substantially aligned in a first direction; At least one adhesive layer including a first adhesive layer; the first adhesive layer is disposed on a first surface of the bulk material; the first adhesive layer is more tacky than the bulk material; the first adhesive layer comprises a second acrylic rubber; the first direction is perpendicular to a first surface of the first face on which the first adhesive layer is disposed; Thermal interface materials.
2. 10. The thermal interface material of claim 1, wherein the first adhesive layer further comprises second filler particles.
3. 3. The thermal interface material of claim 2, wherein the second filler particles comprise graphite.
4. 3. The thermal interface material of claim 2, wherein the second filler particles comprise boron nitride.
5. 10. The thermal interface material of claim 1, wherein a concentration of the second acrylic rubber in the first adhesive layer is greater than a concentration of the first acrylic rubber in the bulk layer.
6. 10. The thermal interface material of claim 1, wherein the concentration of the first acrylic rubber in the bulk layer is greater at a midpoint of the bulk material between a first side of the bulk material and a second side of the bulk material, the second side being opposite the first acrylic rubber.
7. the bulk material includes a second side opposite the first side; a central cross-section of the bulk material having a thickness equal to 50% of a thickness between the first and second sides, the central cross-section having a first average concentration of a first acrylic rubber; an end cross-section of the bulk material corresponding to a cross-section of the bulk material at one of the first surface or the second surface of the bulk material having a thickness equal to 50% of a thickness between the first surface and the second surface has a second average concentration of the first acrylic rubber; 2. The thermal interface material of claim 1, wherein the first average concentration and the second average concentration are different.
8. 8. The thermal interface material of claim 7, wherein a central cross-section of the bulk material is measured such that a central midpoint of the cross-section in a direction between the first surface and the second surface coincides with a midpoint of the bulk material in a direction between the first surface and the second surface.
9. 8. The thermal interface material of claim 7, wherein the first average concentration is greater than the second average concentration.
10. 10. The thermal interface material of claim 1, wherein the first filler particles comprise graphite.
11. 10. The thermal interface material of claim 1, wherein the first filler particles comprise boron nitride.
12. 10. The thermal interface material of claim 1, wherein the plasticizer particles comprise a polyester.
13. 10. The thermal interface material of claim 1, wherein the plasticizer particles have a relatively high molecular weight.
14. 10. The thermal interface material of claim 1, wherein the plasticizer particles have a molecular weight of at least 4,000.
15. 10. The thermal interface material of claim 1, wherein the plasticizer particles have a molecular weight of at least 10,000.
16. 10. The thermal interface material of claim 1, wherein the first acrylic rubber is a self-healing material.
17. 10. The thermal interface material of claim 1, wherein the plasticizer particles have an average viscosity of 850 at 80°C.
18. 2. The thermal interface material of claim 1, wherein the plasticizer particles have a viscosity of 875 to 1025 at 80°C.
19. 2. The thermal interface material of claim 1, wherein the plasticizer particles have a viscosity of 900 to 1000 at 80°C.
20. 10. The thermal interface material of claim 1, wherein the plasticizer particles have an average viscosity of 930 at 25°C.
21. 2. The thermal interface material of claim 1, wherein the plasticizer particles have a viscosity of 825 to 1025 at 25°C.
22. 2. The thermal interface material of claim 1, wherein the plasticizer particles have a viscosity of 850 to 1000 at 25°C.
23. 10. The thermal interface material of claim 1, wherein the plasticizer particles comprise a first set of plasticizer particles and a second set of plasticizer particles, the first set of plasticizer particles and the second set of plasticizer particles being different.
24. 24. The thermal interface material of claim 23, wherein the first set of plasticizer particles has a viscosity of 900-1000 at 80° C. and the second set of plasticizer particles has a viscosity of 850-1000 at 25° C.
25. 24. The thermal interface material of claim 23, wherein the first set of plasticizer particles has a viscosity of 875-1025 at 80° C. and the second set of plasticizer particles has a viscosity of 825-1025 at 25° C.
26. The thermal interface material of claim 1 , wherein the bulk layer includes one or more air channels extending along the first direction.
27. 10. The thermal interface material of claim 1, wherein the bulk layer includes one or more air channels substantially parallel to a direction in which the first filler particles are aligned.
28. 10. The thermal interface material of claim 1, wherein the bulk layer includes one or more air channels substantially parallel to the first direction.
29. 10. The thermal interface material of claim 1, wherein the bulk layer comprises a set of gas pockets, the gas bubbles being aligned substantially perpendicular to a direction in which the first filler particles are aligned.
30. 30. The thermal interface material of claim 29, wherein the gas pockets correspond to air pockets.
31. 10. The thermal interface material of claim 1, wherein the bulk layer has a greater thermal conductivity in a first direction than in a direction perpendicular to the first direction.
32. 10. The thermal interface material of claim 1, wherein the bulk layer has a maximum thermal conductivity in a first direction.
33. 10. The thermal interface material of claim 1, wherein the average molecular weight of the plasticizer particles is greater than an average molecular weight of the first acrylic rubber.
34. 10. The thermal interface material of claim 1 , wherein the at least one adhesive layer comprises a second adhesive layer disposed on a side of the bulk layer opposite the first side of the bulk layer on which the first adhesive layer is disposed.
35. 10. The thermal interface material of claim 1, wherein the first filler particles comprise ceramic particles.
36. 10. The thermal interface material of claim 1, wherein the first filler particles are flat.
37. 10. The thermal interface material of claim 1, wherein the substantial alignment of the first filler particles in a first direction comprises greater than 50% of the first filler particles being aligned in the first direction.
38. 40. The thermal interface material of claim 37, wherein the first filler particles aligned in the first direction include a longest side of the first filler particles parallel to the first direction.
39. The substantial alignment of the first filler particles in a first direction comprises at least 75% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being parallel to the first direction.
40. The substantial alignment of the first filler particles in a first direction comprises at least 85% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being parallel to the first direction.
41. The substantial alignment of the first filler particles in a first direction comprises at least 90% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the alignment of the first filler particles in a first direction comprises a longest side of the first filler particles being parallel to the first direction.
42. The substantial alignment of the first filler particles in a first direction comprises at least 75% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction.
43. The substantial alignment of the first filler particles in a first direction comprises at least 85% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction.
44. The substantial alignment of the first filler particles in a first direction comprises at least 90% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction.
45. The substantial alignment of the first filler particles in a first direction comprises at least 90% of the first filler particles being aligned in the first direction; 10. The thermal interface material of claim 1, wherein the first filler particles being aligned in a first direction comprises a longest side of the first filler particles being within 5 degrees of the first direction.
46. 10. The thermal interface material of claim 1, wherein the first filler particles include a first subset of first filler particles and a second subset of first filler particles.
47. 47. The thermal interface material of claim 46, wherein an average size of a first subset of the first filler particles is greater than an average size of a second subset of the first filler particles.
48. 48. The thermal interface material of claim 47, wherein a thermal conductivity of a first subset of the first filler particles is more uniform than a thermal conductivity of a second subset of the first filler particles.
49. 10. The thermal interface material of claim 1, wherein 80% by weight of the bulk layer is the first filler particles.
50. 10. The thermal interface material of claim 1, wherein a first tensile strength along a first direction of the thermal interface material is different from a second tensile strength along a direction perpendicular to the first direction of the thermal interface material.
51. 10. The thermal interface material of claim 1, wherein the thermal interface material has a tensile strength along a first direction that is less than a tensile strength of the thermal interface material along a direction perpendicular to the first direction.
52. a first tensile strength along a first direction of the thermal interface material that is different from a second tensile strength along a direction perpendicular to the first direction of the thermal interface material; 10. The thermal interface material of claim 1, wherein a ratio of the second tensile strength to the first tensile strength is at least 1.5:
1.
53. a first tensile strength along a first direction of the thermal interface material that is different from a second tensile strength along a direction perpendicular to the first direction of the thermal interface material; 10. The thermal interface material of claim 1, wherein a ratio of the second tensile strength to the first tensile strength is at least 2:
1.
54. a first tensile strength along a first direction of the thermal interface material that is different from a second tensile strength along a direction perpendicular to the first direction of the thermal interface material; 10. The thermal interface material of claim 1, wherein a ratio of the second tensile strength to the first tensile strength is at least 2.5:
1.
55. a first tensile strength along a first direction of the thermal interface material that is different from a second tensile strength along a direction perpendicular to the first direction of the thermal interface material; 10. The thermal interface material of claim 1, wherein a ratio of the second tensile strength to the first tensile strength is at least 3:
1.
56. 10. The thermal interface material of claim 1, wherein the first adhesive layer further comprises second filler particles.